Analisis Pengaruh Pendapatan, Tabungan Dan Konsumsi Tahun Sebelumnya Terhadap Konsumsi Masyarakat Di Indonesia - Diki Setiawan; Syamsul Amar (Jurnal Kajian Ekonomi dan Pembangunan, 2022)
This study examines the analysis of the effect of income, savings and consumption in the previous year on consumption, with the scope of Indonesia. The data used in this study is secondary data obtained from the publications of the relevant agencies. This study uses Panel Regression analysis. The results of the study: (1) The effect of income on consumption is significant and positive, (2) The effect of saving on consumption is negative and not significant, (3) The effect of previous year's consumption on consumption is significant and positive, (4) Simultaneously, the effect of income, saving and consumption of the previous year to the consumption of Indonesian people is significant.